2019
DOI: 10.3892/ijmm.2019.4407
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin regulates the balance between�cardiomyocyte apoptosis and autophagy in chronic heart failure by inhibiting mTOR signaling

Abstract: The progressive loss of cardiomyocytes caused by cell death leads to cardiac dysfunction and heart failure (HF). Rapamycin has been shown to be cardioprotective in pressure-overloaded and ischemic heart diseases by regulating the mechanistic target of rapamycin (mTOR) signaling network. However, the impact of rapamycin on cardiomyocyte death in chronic HF remains undetermined. Therefore, in the current study we addressed this issue using a rat myocardial infarction (MI)-induced chronic HF model induced by liga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
89
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(104 citation statements)
references
References 56 publications
0
89
0
3
Order By: Relevance
“…Therefore, non-eIF4E-mediated mRNA translation plays a major role during ischemia, as most lymphangiogenic factors are translationally induced in hypoxic cardiomyocytes [208][209][210][211]. Finally, consistent with these findings, inhibition of mTORC1 by rapamycin was recently shown to be cardioprotective in pressure-overloaded and ischemic heart diseases, preventing cardiomyocyte apoptosis, and promoting autophagy in chronic heart failure [212].…”
Section: The Mtorc1 Signaling Pathway In Metabolic and Inflammatory Dmentioning
confidence: 54%
“…Therefore, non-eIF4E-mediated mRNA translation plays a major role during ischemia, as most lymphangiogenic factors are translationally induced in hypoxic cardiomyocytes [208][209][210][211]. Finally, consistent with these findings, inhibition of mTORC1 by rapamycin was recently shown to be cardioprotective in pressure-overloaded and ischemic heart diseases, preventing cardiomyocyte apoptosis, and promoting autophagy in chronic heart failure [212].…”
Section: The Mtorc1 Signaling Pathway In Metabolic and Inflammatory Dmentioning
confidence: 54%
“…As an allosteric inhibitor of mTOR complex I (mTORC1), rapamycin plays a role in the suppression of cell growth and division, and has been used as an immunosuppressant drug, or for the treatment of cancer and in-stent restenosis in clinical practice. Rapamycin has also been shown to reduce cardiomyocyte hypertrophy in a mouse model of chronic ischemic injury and to inhibit cardiomyocyte apoptosis in vitro (angiotensin II-induced myocyte apoptosis model) and in vivo (MI-induced chronic heart failure rat model) ( 126 ).…”
Section: Current Developments In Mitochondria-targeted Agents Withmentioning
confidence: 99%
“…Therefore, it has been shown that enhancing autophagy can improve cardiac function and alleviate pathological changes associated with cardiac aging by removing dysfunctional organelles and misfolded proteins. For example, inhibiting Akt/mTORC1 signaling can enhance autophagy, thereby inhibiting cardiac aging [53]. The deletion of Rhoassociated coiled-coil-containing protein kinase (ROCK)1 and ROCK2 reduces cardiac fibrosis during cardiac aging by promoting age-related autophagy in mice [54].…”
Section: Oxidative Stressmentioning
confidence: 99%
“…The second complex is mTOR complex 2 (mTORC2), which is made up of mTOR, Rictor, βl, Sin1, PRR5/Protor-1, and DEPTOR and is insensitive to short-term rapamycin treatment [88]. There is growing evidence that mTOR signaling is activated in many diseases, including cancer [89], neurodegenerative disorders [90], obesity [91], chronic obstructive pulmonary disease [91,92], pulse arterial hypertension [93], and CVD [53].…”
mentioning
confidence: 99%